Analisis Stabilitas Beberapa Konformasi Glisin Melalui Pendekatan Komputasi Kuantum Mekanika Molekuler - Thoriq, Mochammad Ragil (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2025)
This study aims to analyze the stability of various glycine conformations using a quantum computational approach based on molecular mechanics. The methodology involves geometry optimization performed on computational servers, where each conformation is analyzed to obtain the Final Single Point Energy, Loewdin charges, dipole moments, and the energy gap between the Highest Occupied Molecular Orbital (HOMO) and Lowest Unoccupied Molecular Orbital (LUMO). Optimization results reveal stability differences among glycine conformations based on single-point energy values, with Loewdin charge values indicating varied electron distribution across each conformation. The most optimal energy obtained was -284.080 Hartree for the conformation in which the amino group aligns with the carbonyl group. Dipole moment analysis provides insights into conformation polarity, where differences in glycine conformations significantly impact the overall dipole moment. The conformation with the highest polarity features the amino group adjacent to the hydroxyl group, with a dipole moment of 5.58246 Debye. Additionally, the HOMO-LUMO energy gap for each conformation correlates with glycine’s stability and chemical reactivity. This study offers insights into factors influencing glycine stability, such as steric and electronic effects, and aims to support further research on glycine development.